Pendampingan Pembentukan Bank Sampah Ikhlas Oleh Mahasiswa Kukerta Terintegrasi Abdimas Universitas Riau Tahun 2023 - Nurul Amalia; Wan Muhammad Anjeri Fachrowi; Salsabila Ditha Adaira; Ulfa Khairiyah Adha; Muhammad Ichsnuddin; Joleha Joleha; Putri Dwi Wulandari; Elianora Elianora; Kurniawaty Fitri; Rahmi Nur Anisah Nasution; Meliana Siagian; Rizky Anandaku Aksana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
A waste bank is a place where waste is collected and reprocessed with the principle of usefulness (efficiency). In the waste bank the source is household waste and similar household waste. Based on the national waste phenomenon, waste becomes an important problem because waste is an environmental problem and has an impact on health. In this research, the waste problem is seen from a densely populated environment where there is no waste processing site. Basically, waste can be useful if processed properly. The aim of this research is the aim of this service program as a form of environmental care movement by innovating the establishment of a waste bank at the RT 09 RW 03 level as well as solving waste problems in the RT 09 RW 03 environment. The research method used is Community based participatory action is part of Participatory action research. The results of this research are the formation of an Ikhlas Waste Bank in the Putri Tujuh II residential community RT 09 RW 03 West Sidomulyo District as well as an understanding of effective and efficient waste processing.